Technology Entrepreneurship (ENT600) : American Tourister / Nur Fatin Shahirah Mustapa Kamal - Mustapa Kamal, Nur Fatin Shahirah (2021)
This case study presents an overview of smart luggage and displays the problem statement and solution for the problem of this case study. Nowadays, traveler usually only bring their luggage as their main bag companion. A luggage bag is a rectangular shaped looking bag with rounded or square corners, either metal, hard plastic, or made of cloth, vinyl, or leather that more or less retains its shape. This case study was conducted to improve the normal luggage and make it have a more advanced function luggage bag. Travelers usually having a lack of varieties of the function of their bag. This case study is done to understand the basic requirement of traveler ideal luggage bags and features that travelers want to add to their luggage bags. This case study explains the improvement of the luggage bag by putting the safety features and added some extra components on the luggage that can help the luggage becoming more than just a normal luggage bag. Tracker device is added to the luggage bag so it can give extra safety feature to the luggage in the case when traveler misplaces their bag or their bag is snatched by a theft, therefore, they manage to locate the exact location of their luggage bag and also added LED light on the luggage bag so that it can be seen at night. The purpose of this case study is to create a multifunction and features of luggage bag that enable the traveler to have a smooth trip and at the same time luggage bag is more than just a normal luggage bag.